History of the Principle of Transparency in International Trade Law - Darahan, Vladyslav; Дараган, В. (Одеса : Видавничий дім «Гельветика», 2020)
The present article focuses on the evolution of the principle of transparency and its role in international trade law. The basis of the study is the international legal framework for the transparency requirements, most notably GATT 1947 and GATT 1994. The article traces the roots of transparency in international law and analyses its consecutive development throughout the 20th century and early 21st century. Author applied a number of general scientific and specifi c legal methods during the study. They allowed to carry out a comprehensive research 64 and analysis the major international treaties in the area of international trade and their evolving provisions on transparency. Author concludes that transparency has become one of the fundamental provisions in the current WTO system. This is indeed confirmed by the WTO Dispute Settlement Mechanism, which now treats the transparency-related claims as substantive claims. Author shows that it was not the case under the GATT 1947 system, which was inefficient to tackle non-transparent measures that started to occur in early 1970s. As a result, such measures severely impacted bilateral trade between many contracting parties to GATT 1947, mostly between Japan and the United States. Author also shows that the United States were the original architect of the transparency provision in GATT 1947, which was largely based on the American administrative law and was called to create a level playing field for American companies in foreign markets, as the United States provided a high level of transparency domestically. Later on, it was also the United States who advocated for the expansion of the transparency requirements in GATT 1994, and eventually ended up being targeted by numerous transparency-related claims in the framework of the Dispute Settlement Mechanism. Стаття присвячена історичній еволюції принципу прозорості та його ролі у міжнародному торговельному праві. Основою дослідження є міжнародноправова база вимог щодо прозорості, зокрема GATT 1947 та GATT 1994. У статті простежено коріння прозорості у міжнародному праві та проаналізовано її послідовний розвиток упродовж ХХ століття та на початку ХХІ століття. Автор застосував під час дослідження низку загальнонаукових та спеціальних юридичних методів. Вони дозволили провести комплексне дослідження та проаналізувати основні міжнародні договори у сфері міжнародної торгівлі та еволюцію положень щодо прозорості. Автор робить висновок, що прозорість стала одним із основних положень у сучасній системі СОТ. Це підтверджується Механізмом врегулювання спорів СОТ, який зараз розглядає вимоги щодо прозорості як суттєві претензії. Автор відзначає, що це було не так у системі GATT 1947, яка була неефективною для подолання непрозорих заходів, що почали здійснюватися на початку 1970-х. Як результат, такі заходи вагомо вплинули на двосторонній товарообіг між багатьма договірними сторонами GATT 1947, в основному між Японією та США. Автор також зазначає, що Сполучені Штати були оригінальним архітектором положення про прозорість у GATT 1947, яке значною мірою ґрунтувалося на американському адміністративному законодавстві та було покликане створити рівні умови для американських компаній на зовнішніх ринках, оскільки США надавали високий рівень прозорості на внутрішньому рівні. Згодом США також виступали за розширення вимог щодо прозорості у GATT 1994 р., і, врешті-решт, опинилися мішенню для численних вимог, пов’язаних з прозорістю, у рамках Механізму врегулювання спорів.
Darahan V. The History of the Principle of Transparency in International Trade Law / V. Darahan // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". – Одеса : Видавничий дім «Гельветика», 2020. - № 3. – C. 63 - 78. DOI 10.26886/2524-101X.3.2020.4
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; міжнародна торгівля; стаття X GATT 1947; стаття X GATT 1994; історія принципу прозорості; международная торговля; статья X GATT 1947; статья X GATT 1994; история принципа прозрачности; international trade; Article X GATT 1947; Article X GATT 1994; history of the principle of transparency